Establishment of a nutritional rehabilitation evaluation index system for patients with severe spinal deformities based on analytic hierarchy process - Chunyi Liu; Shinan He (Journal of the Pakistan Medical Association, 2025)
Objective: To construct the evaluation index system of nutritional rehabilitation nursing quality for patients with severe spinal deformity, and to provide reference for improving the quality of nutritional rehabilitation nursing. Method: The study was conducted from January 1 to June 30, 2022, in in Henan, Hebei and Shandong provinces of China, and comprised experts in the field of spine orthopaedics, including doctors, nurses and managers from 10 tertiary grade A general hospitals. Data was collected through a predesigned questionnaire. Through literature search, combined with the "structure process result" theoretical model, guided by relevant standards and guidelines, the data was analysed to generate the quality evaluation index system of nutritional rehabilitation nursing for patients with severe spinal deformity using analytic hierarchy process. Statistical analyses was done using SPSS 20. Results:Of the 20 experts, 15(75%) were females and 5(25%) were males. The overall mean age was 38.77±6.65 years (range: 34-55 years). There were 13(65%) head nurses, 5(25%) nursing directors, and 2(10%) attending physicians. Educational levels included undergraduate degrees 11(55%)) and master's degrees or higher 9(45%). The mean clinical experience was 13.55±7.21 years (range: 11-35 years), and mean nursing management experience was 10.11±3.12 years (range: 12-18 years). There were 13(65%) subjects with intermediate-level professional titles, 5(25%) deputy seniors, and 2(10%) with senior titles. The evaluation index system of nutritional rehabilitation nursing quality for patients with severe spinal deformity was divided into three levels, including three first-level indicators, seven second-level indicators and 34 third-level indicators. Conclusion: The evaluation index system of nutritional rehabilitation nursing quality for patients with severe spinal deformity was found to have high reliability, and could be used as an evaluation tool to provide objective and quantifiable indicators. Keywords: Spinal deformity, Nutritional rehabilitation, Analytic hierarchy process, Evaluation index system.